Bringing the benefits of David to Goliath: special economic zones and institutional improvement. Issue 10 (3rd October 2018) - Hartwell, Christopher A.
ABSTRACT: The theory behind special economic zones (SEZs) focuses on their role in overcoming broader policy failings in a country. This paper hypothesizes that the ability of smaller countries to reform more quickly provides a theoretical 'missing link' as to how SEZs can assist reform, developing the idea of SEZs as a 'small country in a large country'. Using a new database, the paper tests this proposition by examining if SEZs have actually been able to spur on institutional improvement in large countries. Results show that SEZs do influence the institutional development of a country, contingent upon prevailing institutional trends.